A comparison of the lubrication behavior of whey protein model foods using tribology in linear and elliptical movement. Issue 4 (14th June 2017) - Campbell, Caroline L.; Foegeding, E. Allen; van de Velde, Fred
Abstract: Lubrication is an important factor in the sensory evaluation of food products. Tribology provides a theoretical framework and instrumental methods for evaluating frictional properties between two moving surfaces and the lubrication behavior of products between these surfaces. Relating frictional measurements to sensory properties detected during oral processing requires careful and pertinent choices in surface materials and testing conditions. The aims of this study were to investigate: (a) differences in lubrication behavior of a range of food textures and (b) the differences between linear and elliptical movement and added saliva to understand the contribution of food structure to friction. Six whey protein model food samples, ranging in texture from fluid to semisolid to soft solid, were analyzed using a pin on disk tribometer to determine the coefficient of friction (COF) across a range of sliding speeds. The samples were analyzed in their initial form and post‐oral processing ( n  = 4) in both linear and elliptical movements. Elliptical movement slightly decreased coefficients of friction and extended the shape of the friction curve. Increases in test food viscosity decreased the COF but differences in viscosity were not apparent when test foods were mixed with saliva. Data correction for viscosity shifted the friction curves horizontally, indicating that lubrication had a greater impact upon friction than viscosity. This study provides initial insights for further comparison of linear and elliptical movement with a variety of sample compositions. Practical applications: Sensory perception of smoothness and creaminess are often major contributors to overall hedonic food liking and are a major reason why products high in fat and sugar are more highly preferred over other foods. These parameters are influenced by friction and lubrication between the tongue, palate, teeth, food products, and saliva during oral processing. Tribology provides an instrumental method to evaluate friction between moving surfaces that mimic oral surfaces and the lubrication behavior of foods. Trends in frictional measurements can be correlated with sensory ratings of the same foods to better understand why preferences exist for certain foods or food compositions and how to effectively improve the acceptability and enjoyment of healthier foods.